The Use of Kahoot Application-Based Interactive Quiz Learning Media as an Effort to Improve Learning Outcomes of Class X Students at SMA Negeri 1 Rimba Melintang - Putri Rahmalasari; Caska Caska; Mujiono Mujiono (Journal of Education Technology Information Social Sciences and Health, 2024)
This study aims to determine the increase in student learning outcomes through the use of interactive quiz learning media based on the kahoot application in class X-1 economics at SMA Negeri 1 Rimba Melintag. This research is a type of Classroom Action Research (CAR). The research subjects were 26 students of class X-1 SMA Negeri 1 Rimba Melintang. The data collection is done through documentation and tests. This study uses two cycles where there are several actions, namely action planning, action implementation, observation, and reflection. Data collection techniques using observation, and learning achievement tests. Based on the results of research on learning outcomes there is an increase in each cycle. In cycle I, the Pre-Test score of 65% (17 students) achieved a score above KKM 70 and 35% (9 students) had not achieved learning completeness, the Post-Test score (22 students) achieved learning completeness and (4 students students) have not yet achieved mastery learning. In cycle II, the Pre-Test score was 73% (19 students) achieving a score above the KKM and 27% (7 students) did not achieve learning completeness, the Post-Test score was 100% (26 students) learning completeness. Thus it can be concluded that the use of interactive quiz media based on the kahoot application can improve the learning outcomes of class X-1 students of SMA Negeri 1 Rimba Melintang.